Kolokyum : 19. yy.’da Mersin ve Akdeniz dünyası : Mersin, Türkiye 18-20 Nisan, 2002 = Mersin, the Mediterranean, and modernity : colloquium heritage of the long nineteenth century : Mersin, Turkey April 18-20, 2002. (Mersin)
155 s.